Hierarchical‐Porous Ceramic Foams by a Combination of Replica and Freeze Technique. Issue 6 (29th March 2019) - Schelm, Katja; Fey, Tobias; Dammler, Kathleen; Betke, Ulf; Scheffler, Michael
Abstract : Open‐porous alumina foams with additional strut porosity are fabricated by a two‐step sponge‐replication based manufacturing process. As the first step, open cellular ceramic foams are prepared following the Schwarzwalder sponge replication technique. Therefore, organic foam templates are coated with different aqueous alumina slurries with a solid load between 20 and 40 vol% In a second step, an additional porosity is generated inside the foam struts by freezing of the foams at temperatures between −196 and −20 °C and subsequent sublimation drying. The hierarchical structure of both, cell pores and strut pores in the freeze‐dried material remains intact after drying, template removal, and sintering. Size, connectivity, and morphology of the strut pores strongly depend on the solid load of the alumina slurry and on the freezing temperature. Cellular structures with a strut porosity between 50% and 60% and a total porosity exceeding 90% are prepared, which show a compressive strength in between 0.4 to 0.6 MPa. Due to the additional strut porosity, the specific surface area of freeze‐dried replica foams increases from 70 cm 2  g −1 for conventionally prepared foams to 200 cm 2  g −1 for freeze‐dried foams, respectively. Abstract : Open‐porous alumina foams with additional strut porosity are fabricated by a two‐step sponge‐replication based manufacturing process. As the first step, open cellular ceramic foams are prepared following the Schwartzwalder technique. In a second step, an additional strut porosity is generated by freezing of the foams and subsequent sublimation drying. Due to the generated strut porosities, the specific surface area of sintered foams could be increased by a factor of three.